(untitled) (Revista de Ciências Agroveterinárias, 2012)
This study evaluates the occurrence of Equine Protozoal Myeloencephalitis (EPM) in the Southern regions of Rio Grande do Sul - Brazil. Sixty-one horses presenting nervous symptomatology were assisted at the Veterinary Clinical Hospital of UFPel. They were subjected to general and specific clinical evaluation and Westernblot analysis in order to identify the presence of Sarcocystis neurona antibodies in the cerebrospinal fluid. Among them, 23 (37.7 %) animals were clinically diagnosed with EPM, 18 (29.5%) of which were positive for Westernblot. The majority of cases occurred in female Thoroughbreds horses with 10 or more years old. The clinical evolution varied, and 61% of the animals responded positively to the therapy.